Predicting Psychosocial Development in College Student-Athletes - Lantz, Christopher D.; Etzel, Edward G.; Ferguson, Kristin J. (My University, 1996)
This study examined the extent to which sport classification, gender, race, and year in school predict psychosocial development in college student-athletes. Eighty-three student-athletes from a NCAA Division I institution completed the Student Developmental Task and Lifestyle Inventory (SDTLI). Senior nonrevenue sport participants reported higher levels of academic autonomy than did any other group, and then African Americans displayed the next greatest level. Gender, race, and year in school were significant predictors of individual psychosocial development on measures of mature interpersonal relationships, educational involvement, and academic autonomy. Counselors, psychologists, and student service providers should be sensitive to these developmental differences when conducting research and devising programming. Suggestions for future research and interventions with student-athletes were presented.
Keywords: academic predictors; Division I; sklls; student development